2020
DOI: 10.1111/petr.13918
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplant in pediatric acute myeloid leukemia: Lessons learnt from a tertiary care center in India

Abstract: The outcomes in pediatric AML have improved consistently over the past three decades, with 5-year EFS rates of 49%-63% and 5-year OS rates of 60%-75%. 1 allo-HSCT is the most effective treatment strategy currently available for children with relapsed or high-risk AML. This curative potential of allo-HSCT is based upon the combination of cytoreduction from conditioning chemotherapy and robust

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(114 reference statements)
0
7
0
Order By: Relevance
“… 14 15 Among children (age ≤ 18 years) with AML who underwent allogeneic HSCT, Arora et al have reported 5-year OS and EFS of 36.3 and 33.3%, respectively. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 15 Among children (age ≤ 18 years) with AML who underwent allogeneic HSCT, Arora et al have reported 5-year OS and EFS of 36.3 and 33.3%, respectively. 16 …”
Section: Discussionmentioning
confidence: 99%
“…14,15 Among children (age ≤ 18 years) with AML who underwent allogeneic HSCT, Arora et al have reported 5-year OS and EFS of 36.3 and 33.3%, respectively. 16 In allogeneic HSCTs, matched donor HSCTs are still preferred over HID-HSCTs; however, advances in graft techniques and pharmacological prophylaxis of GVHD have reduced the risks of graft failure and GVHD after HID-HSCT and have made haploidentical stem cell source a viable alternative for patients lacking an human leukocyte antigen-matched donor. 17 There are no published randomized comparisons of HID HSCT versus MSD HSCT.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…Conventional cytogenetics were done at baseline to identify translocations, inversions, deletion as well as other chromosomal abnormalities for risk stratification of pediatric AML. Mutation profiling of RUNX1-RUNX1T1 (Runt-related transcription factor 1-RUNX1 partner transcriptional co-repressor 1 fusion transcript), CBFB-MYH11 (Core binding factor beta-myosin heavy chain 11 fusion transcript), FLT3-ITD (Fms like tyrosine kinase 3-internal tandem duplication), and NPM1 (Nucleophosmin 1) by reverse transcriptase polymerase chain reaction (PCR) were performed at baseline for risk assessment as per European LeukemiaNet (ELN) recommendation (13).…”
Section: Methodsmentioning
confidence: 99%
“…Consolidation therapy with three cycles of high dose cytarabine at 18g/m 2 were given to patients after achieving complete remission (CR) whereas repeated induction with ADE regimen (cytarabine: 100 mg/m2 twice daily, day 1-10; daunorubicin: 50 mg/m2, day 1-3; and etoposide: 100 mg/m2, day 1-5) were used for refractory or relapse cases. Patients at CR2 underwent allogeneic hematopoietic stem cell transplantation with matched sibling donor if available (13, 14).…”
Section: Methodsmentioning
confidence: 99%
“…In the current cohort of children with relapsed AML, the relapse rate of 46% and 38% deaths are almost similar to data reported by Webb et al 6 where they showed 32% relapse and 41% deaths in children who underwent autologous HSCT in CR2. In our recently published data on allogeneic HSCT in children with AML (which predominantly consisted of subjects with relapsed disease), the 5-year EFS was 33.3 ± 7.2% and OS was 36.3 ± 7.6% 16 ; CR1 duration <12 months was associated with poorer survival. Although CR1 duration did not emerge as a significant predictor of survival in the current study, it is to be noted that only 20% of this cohort had a CR duration of <12 months.…”
Section: Discussionmentioning
confidence: 92%